Tracking Climate Finance What and How? - Clapp, Christa (OECD Publishing, 2012)
Developed countries have committed under the international negotiations to jointly mobilising USD 100 billion per year by 2020 for climate change mitigation and adaptation in developing countries. Yet consistent and comprehensive data to track this commitment are currently lacking. Such data will also help governments and the private sector understand how much and what type of climate finance is flowing today, so as to be able to evaluate progress and effectiveness of international climate finance flows. Estimates based on available data are highly uncertain and incomplete, highlighting several challenges in establishing a robust tracking system. A more political question is what should be the internationally agreed definition of "climate finance" or, absent agreement on that, what types of flows or activities might count towards the USD 100 billion? On the more technical side, challenges include clearly defining flows and sources of international climate finance, determining the cause and effect of flows, and establishing the boundaries of finance flowing towards climate change action. This paper considers what data are currently available to track climate finance, and demonstrates the complex nature of financial flows through examples across international and domestic as well as public and private flows. The examples highlight questions on how to count and track climate finance
Keywords: Energy; Environment